Welcome to my trading room. Volume I, Foundation of trading : basics to trading global shares, futures, and Forex - Magliolo, Jacques (New York, New York : Business Expert Press, 2017)
This volume builds a foundation of knowledge in a comprehensive body of literature on trading to prepare the novice to become a professional trader. This volume starts with the total basics of trading with more in-depth knowledge being explored in the next two volumes.
Part I. Demystifying stock markets -- 1. The enigma of stock markets -- 2. The stock exchange club -- 3. The stockbroking firm -- 4. Investments and shareholders -- Part II. Trading rules for beginners -- 5. Wall Street's golden rules -- 6. Common mistakes and pitfalls -- 7. Common traits of successful traders -- Part III. Portfolio structures -- 8. Money management before trading -- 9. The early years -- Part IV. Streetwise versus experts -- 10. Be street smart -- 11. Market experts -- 12. Markowitz and trading wisdoms -- 13. Traditional portfolio theory -- 14. Steps to the ultimate portfolio -- Appendixes -- Index.
Includes index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: American Stock Exchange; Stocks; Foreign exchange market; Electronic books